Coping Strategies, Anxiety and Depression in OCD and Schizophrenia: Changes during COVID-19 - Ángel Rosa-Alcázar; José Luis Parada-Navas; María Dolores García-Hernández; Sergio Martínez-Murillo; Pablo J. Olivares-Olivares; Ana I. Rosa-Alcázar (Brain Sciences, 2021)
Background: The main aim was to examine changes in coping strategies, anxiety and depression in obsessive–compulsive and schizophrenia patients during COVID-19, in addition to controlling the influence of intolerance to uncertainty and experiential avoidance. Method: The first time, the study comprised (15–30 April 2020) 293 patients, 113 of whom were diagnosed with obsessive–compulsive disorder, 61 with schizophrenia and 119 healthy controls, aged 13–77 years (M = 37.89, SD = 12.65). The second time (15–30 November), the study comprised 195 participants (85 obsessive–compulsive patients, 42 schizophrenic patiens and 77 healthy controls participants). The evaluation was carried out through an online survey. Results: The clinical groups worsened over time in cognitive coping, anxiety and depression, while the control group only worsened in depression. Intergroup differences in anxiety, depression and coping strategies were maintained, highlighting the use of some maladaptive strategies (avoidance, spiritual) in clinical groups. Experiential avoidance and tolerance for uncertainty mainly affected coping. Conclusions: The duration of COVID-19 not only produced changes in anxiety and depression in clinical groups but also in coping strategies to face this pandemic and its consequences.